2015
DOI: 10.1097/nmd.0000000000000378
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Safety and Efficacy of Cranial Electrotherapy Stimulation in Treatment of Bipolar II Depression

Abstract: This double-blind, sham-controlled study sought to investigate the effectiveness of cranial electrotherapy stimulation (CES) for the treatment of bipolar II depression (BD II). After randomization, the active group participants (n = 7) received 2 mA CES treatment for 20 minutes five days a week for 2 weeks, whereas the sham group (n = 9) had the CES device turned on and off. Symptom non-remitters from both groups received an additional 2 weeks of open-label active treatment. Active CES treatment but not sham t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 49 publications
0
14
0
1
Order By: Relevance
“…A number of agents do not have sufficient data to warrant specific recommendations for BDII depression, including cranial electrotherapy stimulation (CES),479 dextromethorphan + quinidine,480 light therapy,481, 482, 483, 484, 485 lisdexamfetamine (adjunctive),300 olanzapine,486 pioglitazone,302 adjunctive pregnenolone,306 celecoxib,297 levetiracetam,487 adjunctive lisdexamfetamine,300 s‐adenosylmethionine,488, 489, 490 acetyl‐ l ‐carnitine + alpha‐lipoic acid,491 adjunctive modafinil,268 rTMS,275, 492, 493 and memantine 494…”
Section: Bipolar II Disordermentioning
confidence: 99%
“…A number of agents do not have sufficient data to warrant specific recommendations for BDII depression, including cranial electrotherapy stimulation (CES),479 dextromethorphan + quinidine,480 light therapy,481, 482, 483, 484, 485 lisdexamfetamine (adjunctive),300 olanzapine,486 pioglitazone,302 adjunctive pregnenolone,306 celecoxib,297 levetiracetam,487 adjunctive lisdexamfetamine,300 s‐adenosylmethionine,488, 489, 490 acetyl‐ l ‐carnitine + alpha‐lipoic acid,491 adjunctive modafinil,268 rTMS,275, 492, 493 and memantine 494…”
Section: Bipolar II Disordermentioning
confidence: 99%
“…However, subsequent studies by Lyon et al (34)(n=167), and Mischoulon et al (35)(n=30) found no advantage of CES over sham on depressive symptoms (all p>.1). One recent pilot study of Bipolar II Depression by McClure et al (36)(n=16) indicated that two weeks of CES could reduce depressive symptoms (p<.003).…”
Section: Section 2: Review Of Published Randomized Controlled Trialsmentioning
confidence: 99%
“…There is one negative study of rTMS ( Nahas et al, 2003 ). There is a small positive study on the usefulness of cranial electrotherapy stimulation in BD-II depression ( McClure et al, 2015 ).…”
Section: Efficacy Datamentioning
confidence: 99%